Non-Linear Lineament Density Impacts on Groundwater Infrastructure for Drought Resilience in Kulon Progo, Indonesia - Susatio, Raja; Arrisaldi, Thema; Aprilia, Faridha; Manek, Emanuel Grace; Wilopo, Wahyu (Universitas Muhammadiyah Surakarta, 2025)
Drought poses a significant threat to water supply in regions like Kulon Progo, Indonesia. Seasonal water shortages lead to agricultural losses and increased disaster vulnerability. This study aims to improve groundwater exploration method for drought mitigation by analyzing the correlation between lineament density and groundwater using a dataset of 127 observations from Samigaluh and Kalibawang subdistricts using Pearson Correlation. The research uncovers a non-linear threshold at 4 km/km². Below the threshold, groundwater occurrence increases with density (r = 0.949), shows increasing infiltration. But above the threshold, occurrence decreases (r = -1.000), suggesting over-fracturing reduces storability. Maximum depths follow a similar pattern (r = 0.883 below, r = -1.000 above). These findings challenge conventional scoring methods in groundwater potential zoning, which often assume a linear positive relationship with lineament density. The study provides a novel framework for targeted exploration, prioritizing moderate-density zones to mitigate drought impacts and build resilience against climate-induced disasters.